Analisis Manajemen Risiko Teknologi Informasi Menggunakan Framework Iso 31000 : Studi Kasus : Aplikasi Kehadiran Mobile (K-MOB) - Rafli Ahmad Zulfikri; Dwi Yuniarto; David Setiadi (STIKes Ibnu Sina Ajibarang, 2025)
Th Advances in information technology have had a significant impact on various aspects of life, including organizational operations. The Mobile Attendance Application (K-Mob) is one implementation of information technology designed to simplify the process of recording attendance in real-time. However, this application is vulnerable to risks that can hamper operations, such as hacking, system failures, and data security issues. This study aims to identify, analyze, and evaluate risks that may affect K-Mob's performance using the ISO 31000 framework. The analysis process is carried out through communication with stakeholders, risk identification, and risk evaluation based on the frequency of occurrence and impact. The results show that significant risks faced include hardware damage, server disruptions, and data misuse. Risk management is carried out through mitigation strategies, such as system updates, infrastructure strengthening, and increasing human resource capacity. With this approach, risks can be minimized, ensuring the sustainability of K-Mob's operations, and improving system reliability. This study recommends regular risk evaluation and the development of adaptive strategies to address evolving threats. The implementation of ISO 31000 has been proven to provide effective guidance in information technology risk management.is.